The quality of government as a determinant of tax compliance behaviour: a proposed model for Bangladesh - Hossain, A M M Masrur; Yussof, Salwa Hana; Isa, Khadijah; Mohd Ghazali, Nazli Anum (Academic Inspired Network, 2023)
Bangladesh, classified by the United Nations (UN) as a Least Developed Country (LDC), largely depends on tax revenue to prepare its national budget. Despite having enormous human and natural resources as well as economic potentials, the country has continued to record one of the lowest tax compliance levels within the South Asian nations. Theoretically, economic factors and other social and behavioural determinants have been discussed to explain the notion of Tax Compliance Behaviour (TCB). However, considering the context of LDCs, the impact of the quality of government (QoG) on TCB has yet to be tested. Furthermore, the inclusion of tax knowledge as a moderator within the tax compliance model might bring more accurate insights into the subject matter. This study proposes a model that includes the QoG, the quality of tax services, economic factors, and tax knowledge as a moderator and incorporate theories from diverse aspects to get an in-depth understanding of the TCB. The proposed model integrates the situational reality of the context as well as the relevant economic, social, and psychological issues to address the compliance behaviour of LDCs, particularly Bangladeshi taxpayers.